2018
DOI: 10.29252/jhsme.5.3.44
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress in Nursing and Its Contributors in the Context of Iran

Abstract: Background and Objectives: Among ultimate goals in the nursing profession are health promotion, disease prevention, and respect for patient rights. In case they are not fulfilled, it can lead to nurses' moral distress, which can have adverse effects on nurses, patients, and the health system. On the other hand, awareness of this concept and its management can help nurses to solve and manage ethical issues in order to be able to continue nursing. Therefore, this study was conducted to obtain the necessary knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…The experiences shared by the study participants also revealed that moral distress often impacted negatively on their wellbeing and work output. Effects that manifested in problems such as stomach problems, nightmares, loss of appetite, frustration, and anger, low work output, demoralization and dissatisfaction are in line with the extant literature 4 , 11 , 12 .…”
Section: Discussionsupporting
confidence: 83%
“…The experiences shared by the study participants also revealed that moral distress often impacted negatively on their wellbeing and work output. Effects that manifested in problems such as stomach problems, nightmares, loss of appetite, frustration, and anger, low work output, demoralization and dissatisfaction are in line with the extant literature 4 , 11 , 12 .…”
Section: Discussionsupporting
confidence: 83%
“…Disregarding the patient's preferences [25], c) Shortage of resources and inappropriate resource allocation and utilization [25], d) Seeing the patient dying without having an opportunity to farewell their relatives and acquaintances [27]. All these factors are consistent with our ndings.…”
Section: Nursing Professionals' Responses To Situations Where Futile Care Is Providedsupporting
confidence: 84%
“…A positive correlation between turnover intention and moral distress was found by Hashemi et al [ 23 ]. Other factors can lead to moral distress, including heavy workload, poor communication with team members or patient and its relatives, limited resources (e.g., staff shortage) [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%